Therapeutic Applications of Nanoformulated Resveratrol and Quercetin Phytochemicals in Colorectal Cancer-An Updated Review - Dhanalekshmi Unnikrishnan Meenakshi; Gurpreet Kaur Narde; Alka Ahuja; Khalid Al Balushi; Arul Prakash Francis; Shah Alam Khan (MDPI AG, 2024)
Natural compounds such as polyphenols play several positive roles in maintaining the oxidative and inflammatory capacity of cells, which leads to their potential use as anticancer therapeutics. There is promising evidence for the in vitro and in vivo anticancer activity of many polyphenols, including resveratrol and quercetin, specifically in the treatment of colorectal cancer (CRC). There is a clear association between resveratrol and quercetin in interfering with the mechanistic pathways involved in CRC, such as Wnt, P13K/AKT, caspase-3, MAPK, NF-κB, etc. These molecular pathways establish the role of resveratrol and quercetin in controlling cancer cell growth, inducing apoptosis, and inhibiting metastasis. The major bottleneck in the progression of the use of resveratrol and quercetin as anticancer therapeutics is their reduced bioavailability in vivo because of their rapid metabolism in humans. Recent advancements in various nanotechnological formulations are promising for overcoming these bioavailability issues. Various nanoformulations of resveratrol and quercetin have shown an optimistic impact on reducing the solubility and improving the stability of resveratrol and quercetin in vivo. A combinatorial approach using nanoformulations of resveratrol with quercetin could potentially increase the impact of resveratrol in controlling CRC cell proliferation. This review discusses the mechanism of resveratrol and quercetin, the two bioactive polyphenolics, in colon cancer, with an emphasis on various types of nanoformulations of the two molecules targeting colon cancer. It also explores the synergistic effect of combining resveratrol and quercetin in various nanoformulations, targeting colon cancer. This research delves into the enhanced pharmacokinetics and potential chemotherapeutic benefits of these bioactive polyphenolics when used together in innovative ways.